Inorganic composition of suspended sediments in the Acre river, Amazon Basin, Brazil (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The purpose of this study was to determine the chemical and mineralogical composition of suspended sediments from the Acre River, located in the Purus Basin, upper Amazon basin, a region associated with the Fitzcarrald Arch. The elemental and mineralogical compositions of the sediments were assessed by using mass and atomic spectroscopy, and X-ray diffraction. A total of 46 samples were collected between 2008 and 2011 from four sites in the study area during wet and dry seasons. The suspended sediments contained feldspar, kaolinite, illite and quartz as well as the elements Hg, Zn, V, Ti, Si, Pb, Ni, Na, Mn, Mg, K, Fe, Cu, Cr, Cd, Ca, Al, S, and P in different proportions that were associated with the various weathering reactions linked to physical, chemical and biological processes in the region. The obtained results represent the first set of values and relationships regarding the mineralogy and chemical identification of the suspended sediments in the Acre River and can be used as a reference for the geochemical characteristics of the Purus Basin. Such regional studies will become increasingly necessary to observe the impacts of climate change and human activities on the suspended sediment load and composition of the Amazon River.